Progressive preoperative pneumoperitoneum in a patient with giant inguinal hernia: report of a case - Huerta-Velázquez, Jose Miguel; Jimenez-Curiel, Alexa; Avalos-González, Guillermo (International Surgery Journal, 2023)
Giant hernias have chronic abdominal wall defects that slowly and progressively grow and alter the normal physiology of the abdominal wall. The clinical case we report is a 76-year-old male who began 7 years ago with protrusion in the left inguinal area with progressive increase in volume until reaching the inability to walk is presented. The protocol is followed by pneumoperitoneum insufflation with 500-1000 milliliters (ml) of carbon dioxide daily for 10 days. The treatment of large hernia defects of the abdominal wall produces a large increase in intra-abdominal pressure during visceral reduction, which entails an alteration in cardiorespiratory biomechanics by elevating the diaphragm and reducing venous return. This technique would be indicated in hernias greater than 10 centimeters (cm), as well as in large inguinal and umbilical hernias, with irreducible sacs, with "loss of domain". It is protocolized with preoperative preparation with pneumoperitoneum for 10 days, for subsequent inguinal plasty with Lichtenstein technique, during which a minimum of adhesions were found, managing to preserve the ipsilateral testicle, reducing surgical time and hospital stay, with no data on compartment syndrome in the abdomen after surgery, providing a good alternative in this type of condition.